Socio-ecological vulnerability: Assessment and coping strategy to environmental disaster in Kedarnath valley, Uttarakhand, Indian Himalayan Region. (October 2017) - Maikhuri, R.K.; Nautiyal, Annpurna; Jha, N.K.; Rawat, L.S.; Maletha, Ajay; Phondani, P.C.; Bahuguna, Y.M.; Bhatt, G.C.
Abstract: Environmental disasters and socio-ecological vulnerability associated with human capacity in any disaster affected region of the world is considered as a key factor in understanding the occurrence of environmental disasters, and consequently, in developing and applying adequate strategies for prevention. The identification of risks and the factors responsible for vulnerability are crucial in analysis and framing strategies for coping and adaptation to the situation. The present paper focuses on identification of potential indicators for disaster risk assessment, socio-economic and cultural vulnerability of local people while striving to cope with shocks of disaster and adaptation and coping strategies of people to mitigate the impact of disaster in Kedarnath valley of Uttarakhand. Based on the long term research and assessment of potential cost-effective bio-resources available locally, this article recommends some of the priority interventions and technology packages for the immediate implementation as well as capacity building of the community to make them economically sustainable and future-ready to respond swiftly towards such catastrophe with less negative impact. Only appropriate strategic framework and their implementation can sustain the human as well as biodiversity in the fragile Himalayan landscape. Graphical abstract: